Performance of The Public Service Bureaucracy: Urban, Rural, and Building Tax Service Model (PBB-P2) Based on Information and Technology - Rahmawati, Rahmawati; Putra, Raniasa (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2024)
The community needs effective, efficient, and accountable public services, including tax services. The Urban & Rural Land & Building Tax (PBB-P2) is a new type of tax for the regions. In the course of its management, there are obstacles and problems. Among them, the community as taxpayers (WP) has difficulty fulfilling their obligations to pay taxes. In addition, the weak administration system of services to taxpayers is due to limited human resources (HR) facilities, infrastructure, organizations, and others. Regional Financial and Asset Management (BPPKAD) considers the bureaucracy too long and prone to deposit discrepancies. The research method used is descriptive research with a qualitative approach. The result of this research is that by innovating in land and building tax services and rural areas (PBB-P2) using information technology, there is an increase in PBB-P2 revenue. There was a significant increase in revenue after the issuance of the PBB-P2 tax authority to the Banyuasin Regency Government, and the increase was due to the program to facilitate the payment of PBB-P2 by the public (taxpayers) using information technology-based services.